Community nutrition in action an entrepreneurial approach - Boyle, Marie A. (Marie Ann) (Cengage Learning, 2017)
"Community Nutrition in Action introduces the program planning, policies, resources, and nutrition issues specific to community nutrition and provides an understanding of creating and implementing nutrition programs from various constituencies (elderly populations, children, impoverished populations, college students, etc.).The book also delivers the core material important to those who will be active in solving community nutritional and health problems, including program delivery, nutrition education, nutrition assessment, and planning nutrition interventions"--Provided by publisher.